A comparative analysis of colonoscopy findings in a Chinese and American tertiary hospital - Wang, He; Cai, Qiang; Zhu, Hong Tao; Lv, Nong Hua; Zhu, Xuan (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: To compare the colonoscopy findings of a tertiary Chinese hospital with those of an American tertiary hospital. Materials and Methods: Hundred consecutive colonoscopies performed in August 2008 at the First Affiliated Hospital of Nanchang University in China and at the Emory University Hospital, United States of America, were investigated. The endoscopic findings and the histopathology results were statistically compared. Results: The average age of Chinese patients who underwent colonoscopy in this study was 45.23±15.38 years, whereas that of American patients was 55.38±12.11 years; no difference in sex ratio was observed (p=0.202) between the two populations. Screening colonoscopy accounted for 38% of patients in the American group and zero patients in the Chinese group. Polyps and diverticula were the most common findings in both groups. Abnormal findings in the American patients were three times higher than those in the Chinese patients. Proximal colon polyps were more common in the American group. Conversely, proximal colon diverticula were more common in the Chinese group. The prevalence of non-neoplasm lesions was not different between the two groups (p=0.232); the prevalence of adenomas significantly increased in patients who were more than 50 years old in both groups and was higher in the American group (p=0.038). Conclusion: The prevalence of bowel diseases in American patients was higher than that in Chinese patients. Polyps and diverticula were the main bowel abnormalities in both groups. Chinese patients lacked awareness of colonoscopy screening and should be enhanced aged 50 years old or older, because the prevalence of advanced neoplasia was increased in this age group in both groups.